Knowledge of Teenagers in Surabaya about COVID-19 and Prevention Behavior - Armyne, Amara Destania; Febriyana, Nining; Retnowati, Wiwin; Karimah, Azimatul (Universitas Airlangga, 2025)
Highlights: Most respondents had good knowledge and prevention behavior. No significant relationship was found between knowledge and behavior to prevent COVID-19. Abstract Introduction: Coronavirus disease (COVID-19) is a newly discovered infectious disease caused by severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), which can affect individuals of all ages. The high positive number of COVID-19 cases in Surabaya and the proportion of teenagers in society is quite large. This study examined the knowledge of teenagers in Surabaya about COVID-19 and prevention behavior. Methods: This descriptive study used a cross-sectional design and an online questionnaire (Google Forms). The target sample was teenagers aged 10-19 years old who live in Surabaya. A total of 122 respondents were involved (n=122). Sampling was performed using the consecutive sampling method, and the data was processed using the International Business Machines Corporation (IBM) Statistical Package for Social Sciences (SPSS) version 19.0 using univariate and bivariate analysis (p=0.367). Results: The results showed that most respondents had good knowledge (72.1%) and good behavior (89.3%) regarding COVID-19. No significant relationship was found between knowledge and behavior to prevent COVID-19 among adolescents who live in Surabaya (p=0.367). Conclusion: This study revealed that most respondents had good knowledge and prevention behavior. Due to a limited number of samples, a larger sample would have provided a more thorough representation of the population and resulted in more accurate outcomes.